Accessories make the outfit: Accessory chromosomes and other dispensable DNA regions in plant-pathogenic fungi - Bertazzoni, S.; Williams, Angela; Jones, D.; Syme, Robert; Tan, Kar-Chun; Hane, James (American Phytopathological Society, 2018)
Fungal pathogen genomes can often be divided into core and accessory regions. Accessory regions ARs) may be comprised of either ARs (within core chromosomes (CCs) or wholly dispensable (accessory) chromosomes (ACs). Fungal ACs and ARs typically accumulate mutations and structural rearrangements more rapidly over time than CCs and many harbor genes relevant to host-pathogen interactions. These regions are of particular interest in plant pathology and include host-specific virulence factors and secondary metabolite synthesis gene clusters. This review outlines known ACs and ARs in fungal genomes, methods used for their detection, their common properties that differentiate them from the core genome, and what is currently known of their various roles in pathogenicity. Reports on the evolutionary processes generating and shaping AC and AR compartments are discussed, including repeat induced point mutation and breakage fusion bridge cycles. Previously ACs have been studied extensively within key genera, including Fusarium, Zymoseptoria, and Alternaria, but are growing in frequency of observation and perceived importance across a wider range of fungal species. Recent advances in sequencing technologies permit affordable genome assembly and resequencing of populations that will facilitate further discovery and routine screening of ACs.